Noble‐Metal‐Free NiS/C3N4 for Efficient Photocatalytic Hydrogen Evolution from Water. Issue 12 (2nd October 2013) - Hong, Jindui; Wang, Yongsheng; Wang, Yabo; Zhang, Wei; Xu, Rong
Abstract A NiS/C3N4 photocatalyst containing earth‐abundant elements only was constructed by means of a simple hydrothermal method. This photocatalyst shows efficient hydrogen evolution (48.2 μmol h−1) under visible light when using triethanolamine as a sacrificial reagent. The optimal loading of 1.1 wt % NiS on C3N4 as a cocatalyst can enhance the H2 production by about 250 times compared with the native C3N4. The highest apparent quantum efficiency of 1.9 % was recorded at 440 nm.